Summer Cash. "Life on the Ice" by Roff Smith. [review] - Wheeler, Tony (Australian Book Review, 2002)
The collapse of the Soviet Union had one quite unexpected effect on world tourism - it opened up Antarctica. Cash-strapped, post-Communist Russia could no longer afford its large collection of Antarctic bases, or the fleet of polar-equipped vessels that supplied them. Many of these ships are now chartered out to adventure travel companies. As a result, the opportunities to visit Antarctica have increased dramatically, while the cost of getting down to the ice has dropped steeply. The Antarctic visitor total is now around 15,000 tourists a year, quite apart from the personnel travelling south to the forty-odd scientific bases. Australia Council, La Trobe University, National Library of Australia, Holding Redlich, Arts Victoria